Brachybacterium subflavum sp. nov., a novel actinobacterium isolated from the foregut of grass carp. Issue 6 (25th June 2021) - Ming, Hong; Cheng, Li-jiao; Yi, Bing-fang; Xia, Ting-ting; Niu, Ming-ming; Zhao, Zi-yu; Liu, Bing-bing; Nie, Guo-xing; Cui, Cai-xia
Abstract : A novel actinobacterium, designated CFH 10395 T, was isolated from the foregut of grass carp ( Ctenopharyngodon idella ), which had been fed with ginseng extract supplement. The taxonomic position was investigated by a polyphasic approach. Cells of CFH 10395 T were Gram-staining-positive, aerobic, ovoid-shaped, non-spore-forming and non-motile. On the basis of the results of 16S rRNA gene sequence analysis, CFH 10395 T was most closely related to Brachybacterium endophyticum KCTC 49087 T, Brachybacterium squillarum JCM 16464 T and Brachybacterium paraconglomeratum JCM 17781 T (97.85%, 97.51 and 97.29% similarity, respectively). CFH 10395 T grew at 4–37 °C, pH 5.0–9.0 and in the presence of up to 10.0 % NaCl (w/v). The dominant menaquinone was MK-7. The whole-cell sugars were rhamnose, glucose, mannose and galactose. meso -diaminopimelic acid was the diagnostic diamino acid in the cell-wall peptidoglycan. The major fatty acids were anteiso-C15 : 0, anteiso-C17 : 0 and iso-C16 : 0 . The genome size was 3.99 Mbp with a DNA G+C content of 71.9 mol%. On the basis of the results of phylogenetic analysis, physiological properties, chemotaxonomic characteristics, low average nucleotide identity (ANI) and digital DDH (dDDH) results [ANI calculated using MUMmer (ANIm) <87 %, ANI calculated using blast (ANIb) <83 % and dDDH <23 %], it is concluded that CFH 10395 T represents a novel species of the genus Brachybacterium, for which the name Brachybacterium subflavum sp. nov., is proposed. The type strain is CFH 10395 T (=CGMCC 1.13804 T =KCTC 49235 T ).